Quantum molecular resonance-assisted phonomicrosurgery: Preliminary experience - Demirhan, Erhan; Çukurova, İbrahim; Arslan, İlker Burak; Özkan, Elçin Tadıhan; Mengi, Erdem; Yiğitbaşı, Orhan Gazi (SAGE Publications, 2015)
The objective of this study was to evaluate the use of quantum molecular resonance (QMR) energy in phonomicrosurgery. Quantum molecular resonance energy (QMRE) is an innovative technology that provides low temperature cutting and coagulation of tissues and causes minimal tissue damage during the procedure. Because of these features, this technology may offer new possibilities in phonomicrosurgery. Twelve patients with vocal fold polyps underwent QMR-assisted phonomicrosurgery. The patients were evaluated before and after surgery at 1 and 3 months postoperatively by using the voice handicap index, laryngeal stroboscopy rating, acoustic voice analysis, and perceptual voice evaluation. The subjects were also evaluated by a patient self-assessment questionnaire at 3 months postoperatively. All parameters significantly improved after QMR-assisted phonomicrosurgery (P < .05). All of the patients also subjectively improved by self-rating. These results suggest that QMRE is a safe and potentially promising treatment in phonomicrosurgery. Yet, further studies should be conducted to confirm these results.
WOS: 000347066300029
PubMed ID: 25214549
Keywords: Voice; Molecular Resonance; Phonomicrosurgery; Vocal Polyp; Stroboscope